Czechoslovakia at the 5th Milan Triennial in 1933 - Hanuš, Ondřej (Vysoké učení technické v Brně, Fakulta architektury, 2021)
The Milan Triennial moved into new exhibition spaces in 1933 and saw a major development in its history. The architecture exhibition presented the audience with an extensive collection of local and foreign productions, as well as the most influential people of the time. The Czechoslovak mission presented more than thirty buildings on its territory. The designs for some of them were published by architectural periodicals, such as Stavba, Stavitel and Forum. These magazines were amongst the selection regularly reported on by Milan’s Casabella, which in the same year, under the leadership of Giuseppe Pagano, decided to accentuate the need to come closer to the European avantgarde approach. The mapping of the main European periodicals on Casabella’s pages made it possible firstly to form a picture of the general foreign architectural situation both in a national and a global context, and secondly to convey it to the Italian audience and the emerging generation of Italian rationalists. The purpose of this work is an analysis of Czechoslovak architecture from the Milan exhibition’s point of view. A second purpose is to map the publishing activities of the foreign section of an influential local medium – Casabella, covering the Czechoslovak architectural scene from 1930 to 1935.
Keywords: Czechoslovakia interwar architecture; Triennale di Milano 1933; Casabella